Cocrystal@protein-anchoring nanococktail for combinatorially treating multidrug-resistant cancer - Jiahui Zou; Xuyang Xing; Chao Teng; Qingling Zhao; Wei He; Xuri Wu; Yuanzheng Xia (Elsevier, 2024)
Multidrug resistance (MDR), the major mechanism by which various cancers develop specific resistance to therapeutic agents, has set up enormous obstacles to many forms of tumor chemotherapy. Traditional cocktail therapy administration, based on the combination of multiple drugs for anti-MDR chemotherapy, often suffers from inconsistent in vivo pharmacokinetic behaviors that cannot act synchronously on the lesions, leading to limited pharmacodynamic outcomes. Despite the emergence of nanomedicines, which has improved chemotherapeutic drugs' bioavailability and therapeutic effect on clinical application, these monotherapy-based nano-formulations still show poor progression in overcoming MDR. Herein, a "one stone and three birds" nanococktail integrated by a cocrystal@protein-anchoring strategy was purposed for triple-payload delivery, which paclitaxel-disulfiram cocrystal-like nanorods (NRs) were anchored with the basic protein drug Cytochrome c (Cyt C), followed by hyaluronic-acid modification. In particular, NRs were utilized as carrier-like particles to synchronously deliver biomacromolecule Cyt C into tumor cells and then promote cell apoptosis. Of note, on A549/Taxol drug-resistant tumor-bearing mice, the system with extraordinarily high encapsulation efficiency demonstrated prolonged in vivo circulation and increased tumor-targeting accumulation, significantly reversing tumor drug resistance and improving therapeutic efficacy. Our mechanistic study indicated that the system induced the apoptosis of Taxol-resistant tumor cells through the signal axis P-glycoprotein/Cyt C/caspase 3. Collectively, this nanococktail strategy offers a promising approach to improve the sensitivity of tumor cells to chemotherapeutic drugs and strengthen intractable drug-resistant oncotherapy.